Percepção ambiental e árvores do cerrado em Gurupi - TO - Silva, Ronaldo Soares da (Universidade Federal do Tocantins, 2019)
Ethnobotanical Studies, if with the vision and popular knowledge about the plants. Considering the few studies carried out in the Cerrado biome, this study aims to analyze the knowledge of the Cerrado plant species and their perceptions by the community of Gurupi-to and the creation of a pedagogical thematic guide as a subsidy for projects of Environmental education. The data collection of perception was made through an online questionnaire and the thematic guide was made from a floristic survey in an area located in the experimental farm of the Federal University of Tocantins of the region. The ranking of the plants was performed according to the Order of citation and the frequency of the citations of each plant to determine the most important species in the Community view. The participants cited 48 species, especially Caryocar brasiliense Camb. (Pequi), Hymenaea coubaril L. (jatoba), Handroanthus spp. (ipê), were the most cited species. The tivities and programs of environmental education in the community are important to potentialize the sustainable use of forest products, to promote the appreciation of the native flora and contribute to its conservation